The impact of global trends on Serbian foreign trade - Stanojevic, Natasa; Kotlica, Slobodan (Industrija, 2020)
This paper analyzes the current key processes in the global economy: decline in international trade, rising protectionism and shortening of global production chains. The specific aim is to investigate the impact of these current trends on Serbian foreign trade. The proposed hypotheses are 1) Decline in the volume of Serbian foreign trade can be expected to be sharper than global indicators and 2) The reduced volume of trade both in Serbia and globally will tend to continue for many years to come. Using statistical analysis for different types of data, linear regression and case study, the research has confirmed the first hypothesis. By applying linear regression, a high correlation between the foreign trade of Serbia and the world of over 90% was determined. The obtained coefficients were applied to the WTO projections for global trade in 2020 and 2021. It was found that the expected decline in Serbia's foreign trade is almost twice the world average. The second hypothesis is proven by the analysis of the economic causes of the main global trends, which have proven to be structural to the greatest extent, hence long-term.
Keywords: international trade, protectionism, global value chains, foreign value added, Serbia